2019
DOI: 10.1007/s10544-019-0407-8
|View full text |Cite
|
Sign up to set email alerts
|

A portable microfluidic platform for rapid determination of microbial load and somatic cell count in milk

Abstract: Microfluidics systems that have been emerged in the last 20 years and used for processing the fluid in a microchannel structure at microliter levels are alternative to the conventional methods. The objective of the study is to develop a microfluidic platform for determination of the microbial load and the number of somatic cells in milk. For this purpose, a polydimethylsiloxane (PDMS) chip with a channel size of 300 μm × 60 μm was produced. Cells/bacteria labeled with fluorescent stain in milk were counted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“…Our system for detecting foodborne pathogens was based on a microfluidic device for on‐chip staining and directly counts the stained bacterial cells flowing in the microchannel. Salmonella Typhimurium in pork was detected using an on‐chip labeling microfluidic device (Wang et al, 2015), and a portable microfluidic system was used to detect E. coli in milk (Düven et al, 2019). A specific feature of our system that differs from other methods is that it enables simple, rapid quantification.…”
Section: Discussionmentioning
confidence: 99%
“…Our system for detecting foodborne pathogens was based on a microfluidic device for on‐chip staining and directly counts the stained bacterial cells flowing in the microchannel. Salmonella Typhimurium in pork was detected using an on‐chip labeling microfluidic device (Wang et al, 2015), and a portable microfluidic system was used to detect E. coli in milk (Düven et al, 2019). A specific feature of our system that differs from other methods is that it enables simple, rapid quantification.…”
Section: Discussionmentioning
confidence: 99%
“…The chamber height of the customized multichamber chip is a very important parameter, which determines whether the milk somatic cells after fluorescent staining can be accurately identified and the accuracy of the cell counting method. Through consulting a large number of milk somatic cell counting articles based on microchamber chips, it was found that the height size of almost all of the microchamber chips involved is 100 μm and below. ,,,, To better study the relationship between the microchamber chip layer height and milk somatic cell count, a batch of cell counting chips was customized by Nanning Matsui Tianlun Company (China), which consisted of a three-layer structure. The bottom layer is a normal glass slide, the middle part is a customized chamber wall structure, which is made of silicone and produced by a customized mold, and the top layer is a glass coverslip.…”
Section: Materials and Methodsmentioning
confidence: 99%
“…Previous studies have shown that highly accurate milk somatic cell counts can be obtained by staining milk somatic cells with fluorescent dyes, which also allows the differentiated analysis of milk somatic cells based on the unique staining characteristics of different milk somatic cell types . In the method of staining milk somatic cells with fluorescent stains, many fluorescent stains can stain the nucleus, such as propidium iodide (PI) stain, DAPI stain, CFDA stain, PYMG stain, PicoGreen stain, and EB stain. , Fluorescence detection is to use an excitation light source to excite the target substance to emit fluorescence at a specific wavelength. Only the target substance will absorb a large amount of excitation light energy and produce a fluorescence effect, thus eliminating the interference of other substances and being less affected by external influences.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al [11] used the coaxial probe technique to collect a dielectric spectra of raw milk to quantify the SCC. Gamze et al [12] performed somatic cell counting on fluorescently labeled raw milk based on a microfluidic platform, achieving an accuracy of more than 80%. P.A.…”
Section: Introductionmentioning
confidence: 99%